PERAN MEDIA SOSIAL DALAM MENINGKATKAN KUALITAS PENDIDIKAN AGAMA ISLAM DI KALANGAN MAHASISWA - Marasabessy, Muhammad Ali Farhan (IMTIYAZ: Jurnal Ilmu Keislaman, 2025)
Social media has emerged as an informal learning space that shapes how university students understand Islamic teachings. This study aims to identify the role of social media in enhancing the quality of Islamic Religious Education (IRE) among students, while also evaluating its challenges and opportunities. This research employs a library research approach, utilizing data from scholarly books, journals, and relevant academic publications. Data were analyzed through content analysis and a comparative-critical approach to theories and prior findings. The results indicate that social media holds significant potential in improving students' Islamic understanding, especially when paired with innovative, value-based pedagogy. However, low digital literacy and the prevalence of entertainment content present major barriers. Lecturers play a crucial role as content curators and facilitators of religious literacy. In conclusion, the integration of social media in IRE must be strategically designed by blending technology with Islamic values to foster a learning experience that is critical, contextual, and spiritual in the digital age.